Enhancing Healthcare Image Security with DNA Cryptography in the IOT Environment - Animesh Kairi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The integration of DNA cryptography into IoT-based healthcare image systems represents a groundbreaking approach to tackle the pressing issue of data security and patient privacy in the digital healthcare landscape. With the increasing reliance on the Internet of Things in healthcare, the need for robust security measures is paramount to protect sensitive medical information. This research explores the feasibility and efficacy of employing DNA cryptography to encode medical data, adding an additional layer of security to data transmitted over IoT networks while ensuring compatibility with existing healthcare infrastructure. By enhancing data integrity, particularly in the realm of E-healthcare, this innovative cryptosystem has the potential to facilitate secure patient data transfer between healthcare institutions, ultimately advancing patient care and preserving privacy. The promising integration of DNA cryptography underscores its potential as a secure and rapid technique, offering a hopeful solution to the security challenges faced by healthcare image systems within IoT environments.